Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph19095693
|View full text |Cite
|
Sign up to set email alerts
|

Stress Detection Using Experience Sampling: A Systematic Mapping Study

Abstract: Stress has been designated the “Health Epidemic of the 21st Century” by the World Health Organization and negatively affects the quality of individuals’ lives by detracting most body systems. In today’s world, different methods are used to track and measure various types of stress. Among these techniques, experience sampling is a unique method for studying everyday stress, which can affect employees’ performance and even their health by threatening them emotionally and physically. The main advantage of experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Non-adjustable parameters consist of sampling rates of 64 Hz for BVP, 4 Hz for EDA, 32 Hz for ACC, and 4 Hz for temperature signals. EDA and BVP signals are also considered to be associated with stress-related physiological signals [6] , [7] , [8] , [9] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Non-adjustable parameters consist of sampling rates of 64 Hz for BVP, 4 Hz for EDA, 32 Hz for ACC, and 4 Hz for temperature signals. EDA and BVP signals are also considered to be associated with stress-related physiological signals [6] , [7] , [8] , [9] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Analyzing and recognizing this particular sort of fatigue, which is an emotion that diminishes situational awareness, the fundamental aspect of human and occupational safety [7] , might help minimize any negative consequences. Currently, the focus of research on emotion recognition often revolves around analyzing physiological information [8 , 9] utilizing artificial intelligence [10] . These experiments demonstrated a significant success rate and found that signals originating from locations directly influenced by the parasympathetic nervous system were more favored.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Nonetheless, first evidence suggests that EMAs could increase precision in the characterisation of at-risk populations [ 50 ], in detecting stressful experiences at the individual level [ 51 ] and in managing major psychiatric disorders, such as depression [ 44 ] or schizophrenic psychoses [ 52 ]. An especially promising approach could be to utilise digital phenotypes for machine-learning-based prediction models in order to define group and individual prognostic trajectories better, to take into account a wider range of influencing factors, to optimise treatments, and to more reliably predict clinical outcomes [ 53 ].…”
Section: The Status Quo Potential and Challenges ...mentioning
confidence: 99%